A SCIENTOMETRIC STUDY OF SCOPUS DATABASE – VETERINARY PUBLICATIONS FROM TAMIL NADU VETERINARY AND ANIMAL SCIENCES UNIVERSITY, CHENNAI - L., Rajendran (International Journal of Research -GRANTHAALAYAH, 2022)
A Scientometric analysis of 2333 Veterinary research articles published in Scopus database has been carried out every year. The individual author’s veterinary publication contributed 204 (7.67%) research documents to the research output. 179 publications on veterinary analysis were published with the help of Indian experts between 1986 and 2020, with a total of 179 papers published in 2011. The Indian Veterinary Journal, with 1280 papers (54.86 %), was the most requested journal, followed by the Indian Journal of Animal Sciences, with 369 papers (15.81%). In the citation distribution, the year 2019 contributed citation has a high rate of 140 (5.07%) referenced in the referred articles. In the distribution of published documents in sponsor research, the Indian Council of Agricultural Research has contributed 29 publications (1.24%) articles. According to the survey, India has 2283 publications (87.85%) of the global Veterinary Science research output out of 10 countries.